Clinical Outcomes and Complications after Open Reduction and Internal Fixation Utilizing Conventional Plates in 65 Distal Radial and Ulnar Fractures of Miniature- and Toy-Breed Dogs - Aikawa, Takeshi; Miyazaki, Yuta; Shimatsu, Taichi; Iizuka, Kyoko; Nishimura, Masaaki (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective This article aims to evaluate clinical outcomes and complications of distal radial and ulnar fractures in miniature- and toy-breed dogs treated with conventional bone plate fixation.Methods Medical records (2001–2010) of miniature- and toy-breed dogs with distal radial and ulnar fractures repaired with open reduction and internal fixation utilizing conventional plates were reviewed. The inclusion criteria were body weight of <7 kg, fracture located in the distal antebrachium (distal-to-total radial length ratio < 0.4) and follow-up radiographs available.Results All 65 fractures healed without developing non-union, and had a successful return to normal function (median follow-up: 73 months; range: 2–149 months). Minor complication in seven fractures and major complication in four fractures were identified.Clinical Significance Open reduction and conventional plate fixation of distal radial and ulnar fractures in miniature- and toy-breed dogs are effective means of fixation that result in normal functional outcome without developing non-union.
Keywords: distal radial and ulnar fracture; conventional plate fixation; miniature- and toy-breed